Pelatihan Gizi Olahraga Untuk Atlet, Pelatih, dan Guru Pendidikan Jasmani - candra kurniawan; Surisman Surisman; Adi S Adi; Dwi Priyono Dwi (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
Sports nutrition is a science that studies the relationship between the management of nutritional needs with performance that is beneficial for health, fitness, growth, and fostering sports achievement. The purpose of this PkM activity is to expand the knowledge and understanding of sports, increase competence and develop skills in compiling the need for good nutritional intake for sports through activities. The method used in this PkM activity uses a lecture approach, discussion, guided practice, and evaluation. Furthermore, this PkM activity provides valuable results and conclusions. It positively impacts various knowledge and understanding of the critical role of sports nutrition for the audience of athletes, sports coaches, and physical education teachers, as well as developing skills in formulating appropriate nutritional intake needs in sports activities.